Effect of Different Finishing and Polishing Agents on the Surface Roughness of Cast Pure Titanium - E. Srinivas Reddy, MDS;1 Narendra P. Patil, MDS;2 (Journal of Prosthodontics, 2007)
The aim of this study was to evaluate the effect of finishing and polishing agents on surface roughness of cast commercially pure titanium using scanning electron microscope (SEM) analysis.